DRO‐MPC‐based data‐driven approach to real‐time economic dispatch for islanded microgrids. Issue 24 (29th October 2020) - Lyu, Cheng; Jia, Youwei; Xu, Zhao
Abstract : Rechargeable battery banks have been widely utilised in islanded microgrids as energy storage systems to complement the instant power imbalance in real‐time. However, the cycle degradation becomes an unavoidable concern of the battery energy storage systems (BESSs) in achieving microgrid economic dispatch (ED). In this study, a novel degradation cost model based on an online auction algorithm is proposed for real‐time management of BESS. To settle the intermittent distributed sources in real‐time operation, a Wasserstein ambiguity set is adopted to characterise the uncertainties. Meanwhile, the authors newly reformulate the real‐time microgrid ED as a two‐stage distributionally robust optimisation (DRO) problem. To improve the tractability and scalability of the DRO problem, a model predictive control (MPC)‐based data‐driven approach is proposed, in which a novel affine policy namely extended event‐wise affine adaption is properly employed. Through extensive case studies, the numerical results demonstrate the effectiveness of the proposed approach.